Zur Koordination im Russischen и, a und дa als als pragmatische Konnektoren - Mendoza, Imke (Slavistische Beitraege, 1996)
In the present work three Russian coordinating connectors are examined, which are very similar in at least one of their partial meanings: they can all be translated with German 'and'. For the connectors 'a' and 'da' in the dictionaries and grammars also a meaning 'but' is given. Another peculiarity of these lexemes is that they exist both as conjunction and as identical particles.